DEVELOPMENT OF HEALTHCARE IN LITHUANIA AND ESTONIA: SIMILAR CONDITIONS, DIFFERENT RESULTS - GUDŽINSKAS, LIUTAURAS (Politologija, 2012)
The article deals with the healthcare systems of Lithuania and Estonia by evaluating their historical context, describing their development after regaining independence, presenting data on how the healthcare resources are distributes, and what are the results of these systems. Although healthcare in these countries is financed at a similar level, the Estonian health system exceeds its Lithuanian (and Latvian) counterparts in many important aspects. It is argued that an essential impact on the differences in the Baltic countries’ healthcare has been exerted by decisions regarding the financing and governance of the health system at the early period of the postcommunist transformation.